Positive electrode active material and preparation method thereof, and battery and electric device containing the positive electrode active material

By forming a sulfur-containing and boron-containing cladding layer on the surface of the positive electrode active material, the impurity removal problem in the prior art is solved, and the material performance and battery performance are improved.

CN115863607BActive Publication Date: 2025-03-25ZHEJIANG GEELY HLDG GRP CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211743963.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-03-25
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

In the prior art, impurities on the surface of the positive electrode active material are difficult to effectively remove, resulting in a degradation of material properties, and the water washing process increases process steps and wastewater problems.

Method used

A lithium-containing metal oxide is used as the base material, and a cladding layer is provided on its surface. The cladding layer is composed of sulfur-containing compounds and boron-containing compounds, and a uniform cladding layer is formed by heat treatment technology.

Benefits of technology

It improves the transmission performance of lithium ions, enhances the circulation and rate performance of the battery, avoids the side reaction between impurities and electrolytes, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115863607B_ABST
    Figure CN115863607B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of secondary batteries, and in particular to a positive electrode active material and a preparation method thereof, as well as a battery and an electrical device containing the positive electrode active material. The positive electrode active material of the present application comprises a lithium-containing metal oxide and a coating layer arranged on the surface of the lithium-containing metal oxide, wherein the coating layer comprises a sulfur-containing compound and a boron-containing compound. The coating layer comprises a sulfur-containing compound and a boron-containing compound to avoid using the sulfur-containing compound alone, so as to control the sulfur-containing compound within a certain range, avoid excessive sulfur-containing compounds causing side reactions between the sulfur-containing compound and the electrolyte, and reduce the service life of the battery. The coating layer comprises a boron-containing compound to further increase the content of the ion-conducting material, so as to improve the cycle performance and rate performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a positive electrode active material and a preparation method thereof, as well as a battery and an electrical device containing the positive electrode active material. Background Art

[0002] The presence of impurities on the surface of the positive electrode active material of a lithium secondary battery may reduce the performance of the positive electrode active material.

[0003] In the prior art, a water washing process is used to remove impurities on the surface of the positive electrode active material. Water washing not only increases the process steps in the preparation process of the positive electrode active material, but also generates waste water. At the same time, in the water washing process, in addition to washing away the impurities on the surface of the positive electrode active material, lithium in the lattice of the positive electrode material may also be lost, thereby reducing the capacity of the positive electrode active material. Summary of the invention

[0004] The main purpose of the present invention is to provide a positive electrode active material, aiming to reduce impurities on the surface of the positive electrode active material and improve the performance of the positive electrode active material.

[0005] To achieve the above object, the present invention provides a positive electrode active material, which includes a lithium-containing metal oxide and a coating layer arranged on the surface of the lithium-containing metal oxide, and the coating layer includes a sulfur-containing compound and a boron-containing compound.

[0006] Optionally, the coating layer partially or fully coats the surface of the lithium-containing metal oxide.

[0007] Optionally, the coating layer has a thickness of 1 nm to 500 nm.

[0008] Optionally, the boron-containing compound includes lithium boron oxide, and the sulfur-containing compound includes lithium sulfur oxide and lithium sulfide.

[0009] The present application also provides a method for preparing a positive electrode active material, comprising the following steps:

[0010] The lithium-containing metal oxide is mixed with a boron compound and a sulfur compound, and subjected to heat treatment to obtain a positive electrode active material;

[0011] The positive electrode active material includes a lithium-containing metal oxide and a coating layer arranged on the surface of the lithium-containing metal oxide, wherein the coating layer includes a sulfur-containing compound and a boron-containing compound.

[0012] Optionally, the mixing amount of the sulfur compound ranges from 0.1wt% to 1.0wt%;

[0013] The mixing amount of the boron compound ranges from 500 ppm to 2000 ppm.

[0014] Optionally, the mixing amount of the sulfur compound ranges from 0.1wt% to 0.5wt%;

[0015] The mixing amount of the boron compound ranges from 500 ppm to 1000 ppm.

[0016] Optionally, the sulfur compound includes K 2 S x O y Or Na 2 S x O y (x=1-8, y=1-8);

[0017] The boron compound includes H 3 BO 3 or B 2 O 3 .

[0018] Optionally, the step of mixing the lithium-containing metal oxide with the boron compound and the sulfur compound and subjecting the mixture to heat treatment to obtain the positive electrode active material includes the following steps:

[0019] The lithium-containing metal oxide is dry-mixed with a boron compound and a sulfur compound, and subjected to heat treatment to obtain a positive electrode active material.

[0020] Optionally, the step of mixing the lithium-containing metal oxide with the boron compound and the sulfur compound and subjecting the mixture to heat treatment to obtain the positive electrode active material includes the following steps:

[0021] The lithium-containing metal oxide is mixed with a boron compound and a sulfur compound, and heat-treated at a temperature of 100° C. to 600° C. in an air or oxygen atmosphere for 2 h to 10 h to obtain a positive electrode active material.

[0022] The present application also provides a battery, comprising: a negative electrode plate, a positive electrode plate, a separator and an electrolyte, wherein the positive electrode plate comprises the positive electrode active material as described, or the positive electrode plate comprises the positive electrode active material prepared by the preparation method of the positive electrode active material.

[0023] The present application also provides an electrical device, which includes the battery.

[0024] The positive electrode active material of the present application includes a lithium-containing metal oxide and a coating layer arranged on the surface of the lithium-containing metal oxide, and the coating layer includes a sulfur-containing compound and a boron-containing compound. The coating layer of the present application includes a sulfur-containing compound and a boron-containing compound, both of which are ion-conducting materials, which can improve the transmission performance of lithium ions during the use of the battery, thereby improving the cycle performance and rate performance of the battery; theoretically, the surface of the lithium-containing metal oxide is coated with an appropriate amount of ion-conducting material, and its lithium ion transmission performance can be maximized; the coating layer includes a sulfur-containing compound and a boron-containing compound, and the use of the sulfur-containing compound alone is avoided, so as to control the sulfur-containing compound within a certain range, and avoid the excessive sulfur-containing compound causing a side reaction with the electrolyte, thereby reducing the service life of the battery. The coating layer includes a boron-containing compound, and the content of the ion-conducting material is further increased to improve the cycle performance and rate performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0026] Figure 1 Schematic diagram of the process for preparing the positive electrode active material of the present invention;

[0027] Figure 2 The Li on the surface of the positive electrode active material under different sulfur compound / boron compound contents of the present invention is 2 CO 3 Residue test chart;

[0028] Figure 3 This is a test diagram of the residual amount of LiOH on the surface of the positive electrode active material at different contents of sulfur compounds / boron compounds of the present invention;

[0029] Figure 4 This is a test diagram of the reagents consumed in the process of testing residual lithium in the present invention.

[0030] Figure 5 This is a discharge specific capacity test diagram of the present invention at different contents of sulfur compound / boron compound;

[0031] Figure 6 This is an electrochemical impedance test diagram of the positive electrode active material of the present invention.

[0032] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Hereinafter, the embodiments of the positive electrode active material and the preparation method thereof of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0035] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0036] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0037] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0038] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0039] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0040] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0041] The presence of impurities on the surface of the positive electrode active material of a lithium secondary battery may reduce the performance of the positive electrode active material.

[0042] For example, when preparing high-nickel ternary materials, there are structural stability issues during the synthesis process. Therefore, in order to synthesize in a stable oxide form, an excess of Li / Me (alloying element) conditions are usually designed to synthesize a positive electrode active material with a stable structure. That is, in the process of preparing high-nickel ternary materials, the mixed ternary precursor and lithium salt have an excess of lithium salt. The excess of lithium salt makes the excess part of the lithium salt not participate in the reaction, so that the lithium salt will react with moisture and CO in the air. 2 The reaction generates residual lithium (LiOH and Li 2 CO 3 ), when manufacturing batteries, the presence of residual lithium will cause many problems, for example, the residual lithium has poor ion conductivity, and its formation on the surface of the ternary material will hinder the transmission of lithium ions in the ternary material, and Li 2 CO 3 It will react with the electrolyte to generate gas and heat, affecting the safety of the battery.

[0043] In the prior art, a water washing process is used to remove residual lithium on the surface of the positive electrode active material. Water washing not only increases the process steps in the preparation process of the positive electrode active material, but also generates waste water. At the same time, during the water washing process, in addition to washing away the residual lithium on the surface of the positive electrode active material, lithium in the positive electrode material lattice may also be lost, thereby reducing the capacity of the positive electrode active material.

[0044] In order to reduce impurities in positive electrode active materials, such as residual lithium, the present application provides a positive electrode active material to reduce impurities and improve the performance of the positive electrode active material.

[0045] The positive electrode active material of the present application includes a lithium-containing metal oxide and a coating layer arranged on the surface of the lithium-containing metal oxide, and the coating layer includes a sulfur-containing compound and a boron-containing compound. The coating layer of the present application includes a sulfur-containing compound and a boron-containing compound, both of which are ion-conducting materials, which can improve the transmission performance of lithium ions during the use of the battery, thereby improving the cycle performance and rate performance of the battery; theoretically, the surface of the lithium-containing metal oxide is coated with an appropriate amount of ion-conducting material, and its lithium ion transmission performance can be maximized; the coating layer includes a sulfur-containing compound and a boron-containing compound, and the use of the sulfur-containing compound alone is avoided, so as to control the sulfur-containing compound within a certain range, and avoid the excessive sulfur-containing compound causing a side reaction with the electrolyte, thereby reducing the service life of the battery. The coating layer includes a boron-containing compound, and the content of the ion-conducting material is further increased to improve the cycle performance and rate performance of the battery.

[0046] Theoretically, the surface of lithium-containing metal oxides is coated with an appropriate amount of ion-conducting materials, and its lithium ion transmission performance can be improved to the greatest extent. Studies have shown that a certain amount of sulfur-containing compounds as lithium-ion-conducting materials can improve battery performance, but when the amount of sulfur-containing compounds exceeds a certain amount, the sulfur-containing compounds will react with the electrolyte, resulting in electrolyte consumption and decomposition of the sulfur-containing compounds. The consequence of this side reaction is the opposite, which reduces the performance of the battery. Therefore, the content of sulfur-containing compounds as the coating layer of lithium-containing metal oxides needs to be controlled within a certain range.

[0047] On the one hand, it is necessary to avoid increasing the content of sulfur-containing compounds in the coating layer, and on the other hand, it is hoped to improve the ion-conducting materials in the coating layer to improve the performance of the battery. The present application further includes a boron-containing compound in the coating layer. On the one hand, the boron-containing compound can be coated on the surface of the lithium-containing metal oxide as an ion-conducting material to improve the transmission performance of lithium ions in the lithium-containing metal oxide and improve the performance of the battery. On the other hand, the boron-containing compound will not react with other components in the battery (such as electrolytes), and the appropriate amount of the boron-containing compound can be adjusted to maximize the performance of the battery.

[0048] That is, a coating layer including a sulfur-containing compound and a boron-containing compound is used to avoid using the sulfur-containing compound alone, so as to control the sulfur-containing compound within a certain range and avoid excessive sulfur-containing compounds causing side reactions with the electrolyte, thereby reducing the service life of the battery. The coating layer includes a boron-containing compound to further increase the content of the ion-conducting material, thereby improving the cycle performance and rate performance of the battery.

[0049] Furthermore, the coating layer partially or completely coats the surface of the lithium-containing metal oxide.

[0050] In the present application, the coating layer may be partially or completely coated on the surface of the lithium-containing metal oxide. In theory, through the experiments in the embodiments, it can be seen that there is still residual lithium (LiOH and Li 2 CO 3 ) exists, based on Li 2 CO 3 Reacts with electrolyte to produce CO 2 , resulting in battery expansion. In the present application, the boron-containing compound can be adjusted to control the coating layer to partially or fully coat the surface of the lithium-containing metal oxide. In this way, the residual Li in the lithium-containing metal oxide can be expanded by the coating layer. 2 CO 3 Coating to avoid Li 2 CO 3 Direct contact with the electrolyte to reduce the residual Li in the lithium-containing metal oxide 2 CO 3 The reaction with the electrolyte reduces the expansion of the battery, reduces the heat generated by the reaction between the electrolyte and residual lithium, improves the characteristics of the battery under high pressure, and improves the safety of the battery.

[0051] Furthermore, the coating layer has a thickness of 1 nm to 500 nm.

[0052] On the one hand, if the coating layer is too thick, it will increase the resistance and limit the transmission of lithium ions. If the coating layer is too thin, the ion-conducting material is insufficient and it is difficult to effectively conduct lithium ions. Therefore, the thickness of the coating layer is 1nm to 500nm. Within this range, the transmission performance of lithium ions is optimal. On the other hand, it is also necessary to avoid the coating layer being too thin, which is difficult to effectively block the residual Li 2 CO 3 and electrolytes.

[0053] In the above-mentioned 1nm to 500nm, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 1nm, 5nm, 10nm, 15nm, 20nm, 30nm, 50nm, 80nm, 100nm, 120nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, etc.

[0054] Further, the boron-containing compound includes lithium boron oxide, and the sulfur-containing compound includes lithium sulfur oxide and lithium sulfide.

[0055] In the present application, the boron-containing compound includes lithium boron oxide, and the sulfur-containing compound includes lithium sulfur oxide and lithium sulfide. 3 BO 3 , lithium oxysulfide including Li 2 SO 4 .

[0056] Lithium sulfide can be used as a lithium supplement. When lithium consumption decreases during the cycle, lithium sulfide can be used as a lithium source to supplement lithium, thereby increasing the capacity of lithium. Compared with the use of boron-containing compounds alone, the coating layer of the present application adopts a combination of boron-containing compounds and sulfur-containing compounds, and the sulfur-containing compounds also include lithium sulfide, which not only improves the ion-conducting material to improve the battery performance, but also further improves the battery capacity, which helps to increase the battery life.

[0057] The present application also provides a method for preparing the above-mentioned positive electrode active material, comprising the following steps: mixing a lithium-containing metal oxide with a boron compound and a sulfur compound, and performing heat treatment to obtain a positive electrode active material; the positive electrode active material comprises a lithium-containing metal oxide and a coating layer arranged on the surface of the lithium-containing metal oxide, and the coating layer comprises a sulfur-containing compound and a boron-containing compound.

[0058] like Figure 1 As shown, in the above preparation process, the lithium-containing metal oxide is mixed with the boron compound and the sulfur compound and subjected to heat treatment. In the process, the residual lithium on the surface of the lithium-containing metal oxide reacts with the boron compound and the sulfur compound, thereby consuming the residual lithium, thereby reducing the content of the residual lithium, that is, the residual lithium is converted into sulfur-containing compounds and boron-containing compounds. While reducing the residual lithium, the ion-conducting material is increased on the surface of the lithium-containing metal oxide. The positive electrode active material prepared by the above method is based on the residual lithium (LiOH and Li 2 CO 3 ) decreases, Li 2 CO 3 Reacts with electrolyte to produce CO 2The problem of battery expansion is improved, and the ion conductivity of the positive electrode active material is improved based on the increase of the sulfur-containing compound and the boron-containing compound of the ion-conductive material.

[0059] Specifically, during the heat treatment process, the lithium-containing metal oxide reacts with the boron compound and the sulfur compound respectively to generate a sulfur-containing compound and a boron-containing compound, and the product is coated on the surface of the lithium-containing metal oxide as a coating layer; since the boron compound has a relatively low melting point, for example, H 3 BO 3 or B 2 O 3 It melts at around 170°C. During the heat treatment, H 3 BO 3 or B 2 O 3 The product is uniformly coated on the surface of the lithium-containing metal oxide after melting; and the boron-containing compound in the coating layer does not react with the electrolyte. The boron compound can be uniformly distributed on the surface of the lithium-containing metal oxide during the heat treatment process by increasing the amount of the boron compound, thereby making the coating layer uniformly distributed on the surface of the lithium-containing metal oxide to obtain a uniform coating layer. The uniform coating layer can avoid the local coating layer from being too thick, which will cause the excessively thick coating layer to form an obstacle and reduce the transmission of lithium ions. The uniformly distributed coating layer makes the lithium-ion transmission effect of the lithium-containing metal oxide better as a whole.

[0060] When the amount of sulfur compound increases to a certain level, the generated sulfur-containing compound will react with the electrolyte to reduce the performance of the battery. That is, in the process of using sulfur compounds alone to form a coating layer, due to the limited amount of sulfur compounds, the generated sulfur-containing compound cannot be evenly coated on the surface of the lithium-containing metal oxide. When the sulfur compound and the lithium-containing metal oxide are heat-treated alone, the resulting coating layer is in the shape of an island and is unevenly distributed on the surface of the lithium-containing metal oxide. That is, the surface of the lithium-containing metal oxide is only partially formed with a coating layer, and the local lithium ion transmission effect is better, and the overall lithium ion transmission effect of the lithium-containing metal oxide needs to be improved.

[0061] That is, the present application obtains a positive electrode active material by mixing a lithium-containing metal oxide with a boron compound and a sulfur compound and performing a heat treatment, wherein the positive electrode active material includes a lithium-containing metal oxide and a coating layer arranged on the surface of the lithium-containing metal oxide, wherein the coating layer includes a sulfur-containing compound and a boron-containing compound; by simultaneously using a boron compound and a sulfur compound to react with residual lithium in the lithium-containing metal oxide, not only the ion-conductive substance in the coating layer is increased, but also the obtained coating layer is uniformly distributed on the surface of the lithium-containing metal oxide, thereby improving the overall lithium ion transport performance of the lithium-containing metal oxide, and the performance of the battery is further improved compared to the use of the sulfur compound alone.

[0062] In addition, sulfur compounds react with lithium carbonate to form carbonate (K 2 CO 3 、Na 2 CO 3 ), carbonates are highly reactive with water and are substances that increase alkalinity. 2 CO 3 、Na 2 CO 3 Within a certain content range, it can serve as a factor to improve the gelation of the slurry during the preparation of the positive electrode slurry, and is helpful in the preparation of the active layer in the positive electrode plate; that is, the simultaneous use of lithium-containing metal oxides with boron compounds and sulfur compounds for heat treatment reactions can not only improve the coating uniformity of the coating layer to improve the overall lithium ion conductivity of the lithium-containing metal oxide, but also help in the preparation of the active layer in the positive electrode plate.

[0063] In summary, the positive electrode active material prepared by the above method includes a lithium-containing metal oxide and a coating layer arranged on the surface of the lithium-containing metal oxide, the coating layer includes a sulfur-containing compound and a boron-containing compound, and the sulfur-containing compound and the boron-containing compound are both ion-conductive materials, which can improve the lithium ion transmission performance during the use of the battery, thereby improving the battery's cycle performance and rate performance; theoretically, the surface of the lithium-containing metal oxide is coated with an appropriate amount of ion-conductive material, and its lithium ion transmission performance can be maximized; the coating layer includes a sulfur-containing compound and a boron-containing compound, and the use of the sulfur-containing compound alone is avoided, so as to control the sulfur-containing compound within a certain range, and avoid the excessive sulfur-containing compound causing side reactions with the electrolyte, thereby reducing the service life of the battery; the coating layer includes a boron-containing compound, and the content of the ion-conductive material is further increased to improve the battery's cycle performance and rate performance.

[0064] Furthermore, in the above preparation process, the morphology of the coating layer in the prepared positive electrode active material can be adjusted by adjusting the amount of the boron compound, that is, the coating layer can be partially coated or fully coated on the surface of the lithium-containing metal oxide.

[0065] Theoretically, it can be seen from the experiments in the examples that there is still residual lithium (LiOH and Li 2 CO 3 ) exists, based on Li 2 CO 3 Reacts with electrolyte to produce CO 2 , resulting in battery expansion. In the present application, the boron-containing compound can be adjusted to control the coating layer to partially or fully coat the surface of the lithium-containing metal oxide. In this way, the residual Li in the lithium-containing metal oxide can be expanded by the coating layer. 2 CO 3 Coating to avoid Li 2 CO 3 Direct contact with the electrolyte to reduce the residual Li in the lithium-containing metal oxide 2 CO 3 The reaction with the electrolyte reduces the expansion of the battery and improves the safety of battery use.

[0066] Furthermore, in the above preparation process, the thickness of the coating layer in the prepared positive electrode active material can be adjusted by adjusting the amount of the boron compound, that is, the thickness of the coating layer is 1 nm to 500 nm.

[0067] On the one hand, if the coating layer is too thick, it will increase the resistance and limit the transmission of lithium ions. If the coating layer is too thin, the ion-conducting material is insufficient and it is difficult to effectively conduct lithium ions. Therefore, the thickness of the coating layer is 1nm to 500nm. Within this range, the transmission performance of lithium ions is optimal. On the other hand, it is also necessary to avoid the coating layer being too thin, which is difficult to effectively block the residual Li 2 CO 3 and electrolytes.

[0068] Furthermore, the mixing amount of the sulfur compound ranges from 0.1wt% to 1.0wt%; the mixing amount of the boron compound ranges from 500ppm to 2000ppm.

[0069] The mixing amount of the sulfur compound is in the range of 0.1wt% to 1.0wt%, while the total weight of the positive electrode active material is 100wt%. When the mixing amount of the sulfur compound is less than 0.1wt%, the residual lithium reduction effect is not good. When the added amount of the sulfur compound is greater than 1wt%, although the residual lithium is reduced, the battery cycle performance is reduced due to the side reaction between the sulfur compound and the electrolyte. Therefore, the mixing amount of the sulfur compound is in the range of 0.1wt% to 1.0wt%.

[0070] Furthermore, the residual lithium (LiOH and Li 2 CO 3 ) reacts with sulfur compounds to form other products (for example, when the sulfur compound is K2 S x O y Or Na 2 S x O y When the other product is K 2 CO 3 Or Na 2 CO 3 ), the generated K2CO3, Na2CO3, etc. are deliquescent substances, have alkalinity, and are highly reactive with water. As substances that increase alkalinity, K 2 CO 3 Or Na 2 CO 3 Within a certain content, it can be used as a factor to improve the gelation of the slurry during the preparation of the positive electrode slurry. Further increase will have a counter-effect, that is, excessive K 2 CO 3 Or Na 2 CO 3 The slurry loses fluidity and cannot be coated on the current collector, which is not conducive to the coating of the active layer of the positive electrode plate. Therefore, the mixing amount of the sulfur compound ranges from 0.1wt% to 1.0wt%.

[0071] The range of the mixing amount of the boron compound is 500ppm-2000ppm. When the mixing amount of the boron compound is less than 500ppm, the residual lithium reduction effect is not good. When the mixing amount of the boron compound is greater than 2000ppm, although the residual lithium can be reduced, at this time, the coating layer will become thicker, which will form an obstacle and reduce the lithium ion transmission. Moreover, further increasing the boron compound is not only not conducive to the lithium ion transmission, but also the boron compound will cause the residual lithium (LiOH and Li 2 CO 3 ) is converted to Li 3 BO 3 , Li 3 BO 3 The molecular weight is higher than Li 2 CO 3 and LiOH, so that the mass capacity of the positive electrode active material is reduced, therefore, the preferred mixing amount of the boron compound is in the range of 500ppm-2000ppm.

[0072] In the above-mentioned 0.1wt% to 1.0wt%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, etc.

[0073] In the above 500ppm-2000ppm, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 500ppm, 600ppm, 800ppm, 1000ppm, 1200ppm, 1500ppm, 1700ppm, 1900ppm, 2000ppm, etc.

[0074] Furthermore, the mixing amount of the sulfur compound is in the range of 0.1 wt% to 0.5 wt%; the mixing amount of the boron compound is in the range of 500 ppm to 1000 ppm.

[0075] The addition amount of sulfur compound is greater than 0.5wt%, which increases the sulfur-containing compound in the coating layer. When the sulfur content rises above a certain value, the sulfur-containing compound reacts with the electrolyte, which reduces the battery life performance. Therefore, when the addition amount of sulfur compound is less than 0.5wt%, it is not only beneficial to the residual lithium reduction performance, but also beneficial to the electrochemical performance. The preferred range of the mixing amount of sulfur compound is 0.1wt% to 0.5wt%.

[0076] The mixing amount of the boron compound ranges from 500ppm to 1000ppm. When the boron compound is controlled within the above range, the obtained coating layer is evenly distributed on the surface of the lithium-containing metal oxide, and the overall performance of the obtained positive electrode active material is improved.

[0077] In the above 0.1wt% to 0.5wt%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, etc.

[0078] In the above 500ppm-1000ppm, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 500ppm, 600ppm, 800ppm, 1000ppm, etc.

[0079] Furthermore, the sulfur compound includes K 2 S x O y Or Na 2 S x O y (x = 1 to 8, y = 1 to 8); boron compounds include H 3 BO 3 or B 2 O 3 .

[0080] Sulfur compounds are used to react with residual lithium (LiOH and Li 2 CO 3 ) reaction, reducing the residual lithium content, increasing the ion-conducting substances, sulfur compounds including K 2 S x O y Or Na 2 S x O y (x=1-8, y=1-8), for example, it can be K 2 S 2 O 3 、Na 2 S 2 O 3 , the reaction formula is nLiOH+nK 2 S x O y ->nLi 2 S+nLi 2 SO x +nH 2 O(n=integer);nLi 2 CO 3 +nK 2 S x O y ->nK 2 CO 3 +nLi 2 S x O y (n = integer); nLiOH + nNa 2 S x O y ->nLi 2 S+nLi 2 SO x +nH 2 O(n=integer);nLi2CO3+nNa2SxOy->

[0081] nNa2CO3+nLi2SxOy (n=integer).

[0082] Boron compounds are used to react with residual lithium (LiOH and Li 2 CO 3 ) reaction, reducing the residual lithium content, increasing the ion-conducting substances, boron compounds including H 3 BO 3 or B 2 O 3 , the reaction formula is nLiOH+nB 2 O 3 ->nLi 3 BO 3 +nH 2O(n=integer);nLi 2 CO 3 +nB 2 O 3 ->nLi 3 BO 3 +nCO 2 (n = integer).

[0083] Furthermore, the step of mixing the lithium-containing metal oxide with a boron compound and a sulfur compound and subjecting the mixture to heat treatment to obtain a positive electrode active material includes the following steps: dry mixing the lithium-containing metal oxide with a boron compound and a sulfur compound and subjecting the mixture to heat treatment to obtain a positive electrode active material.

[0084] The step of mixing the lithium-containing metal oxide with the boron compound and the sulfur compound and performing heat treatment to obtain the positive electrode active material includes the following steps: dry mixing the lithium-containing metal oxide with the boron compound and the sulfur compound and performing heat treatment to obtain the positive electrode active material. Dry mixing refers to mixing without the participation of solvents, such as dry mixing by grinding, ball milling or stirring. Dry mixing saves costs compared to wet mixing.

[0085] Furthermore, in the step of mixing the lithium-containing metal oxide with the boron compound and the sulfur compound and subjecting the mixture to heat treatment to obtain the positive electrode active material, the following steps are included: mixing the lithium-containing metal oxide with the boron compound and the sulfur compound and subjecting the mixture to heat treatment for 2 h to 10 h at a temperature of 100° C. to 600° C. in an air or oxygen atmosphere to obtain the positive electrode active material.

[0086] The step of mixing the lithium-containing metal oxide with a boron compound and a sulfur compound and subjecting the mixture to heat treatment to obtain a positive electrode active material includes the following steps: mixing the lithium-containing metal oxide with a boron compound and a sulfur compound and subjecting the mixture to heat treatment for 2 hours to 10 hours at a temperature of 100° C. to 600° C. in an air or oxygen atmosphere to obtain a positive electrode active material.

[0087] In the above-mentioned 100℃~600℃, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 100℃, 150℃, 200℃, 250℃, 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, 600℃, etc.

[0088] In the above 2h~10h, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 2h, 3h, 4h, 5h, 6h, 7h, 8h, 8h, 10h, etc.

[0089] It can be understood that before the present method is used to remove the residual lithium on the surface of the lithium-containing metal oxide, the residual lithium content on the surface of the lithium-containing metal oxide may exceed 9000 ppm. The positive electrode active material prepared by the present method can significantly reduce the residual lithium content in the positive electrode active material.

[0090] The present application also provides a cathode electrode sheet, which includes a current collector and a positive electrode active material disposed on the current collector. Since the positive electrode active material adopts all the technical solutions of all the above embodiments, it at least has all the beneficial effects brought by the technical solutions of the above embodiments, which will not be repeated here one by one.

[0091] The present application also provides a battery, comprising: a negative electrode plate, a positive electrode plate, a separator and an electrolyte, wherein the positive electrode plate comprises the positive electrode active material as described above, or the positive electrode plate comprises the positive electrode active material prepared by the preparation method of the positive electrode active material as described above. Since the positive electrode active material adopts all the technical solutions of all the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be repeated here one by one.

[0092] The present application also provides an electrical device, which includes the above-mentioned battery. Since the battery adopts all the technical solutions of all the above-mentioned embodiments, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.

[0093] Example

[0094] Example 1

[0095] Preparation of lithium-containing metal oxides

[0096] Take the ternary precursor Ni 0.83 Co 0.12 Mn 0.05 (OH) 2 The mixture is uniformly mixed with an excess amount of lithium salt, sintered at a high temperature of 800° C. in a muffle furnace under an oxygen atmosphere for 10 hours, crushed and sieved to obtain a lithium-containing metal oxide.

[0097] Preparation of positive electrode active materials

[0098] The lithium-containing metal oxide prepared above and the boron compound B 2 O 3 and sulfur compound K 2 S 2 O 3 Dry mixing, B 2 O 3 The concentration in the mixture is 1000ppm, K 2 S 2 O 3The concentration in the mixture is 1.0wt%, and the mixture is heat treated at 350°C in an oxygen atmosphere for 5 hours to obtain a positive electrode active material; the positive electrode active material includes a lithium-containing metal oxide and a coating layer arranged on the surface of the lithium-containing metal oxide, and the coating layer includes a sulfur-containing compound and a boron-containing compound.

[0099] The positive electrode active material prepared as above is used to prepare a positive electrode sheet, and the positive electrode sheet is assembled into a battery with a negative electrode sheet, a separator, an electrolyte, etc., and a performance test is performed.

[0100] Comparative Example 1

[0101] Different from Example 1, the prepared lithium-containing metal oxide is directly used in battery preparation.

[0102] Comparative Example 2

[0103] Different from Example 1, during the preparation of the positive electrode active material, the lithium-containing metal oxide prepared above and the sulfur compound K 2 S 2 O 3 Dry mixing, K 2 S 2 O 3 The concentration of the mixture was 0.1 wt % and the mixture was heat treated at 350° C. in an air atmosphere for 5 h to obtain a positive electrode active material.

[0104] Comparative Examples 3 to 5

[0105] The difference from Comparative Example 1 is that the K 2 S 2 O 3 The concentrations in the mixture were 0.2wt%, 0.5wt% and 1.0wt% respectively.

[0106] Residual LiOH, LiCO 3 Test

[0107] The residual LiOH and LiCO were tested by acid-base titration. 3 .

[0108] First discharge specific capacity test

[0109] The prepared battery was subjected to charge and discharge cycle test at 60°C, 0.1C charge and discharge, and a charge and discharge cut-off voltage of 2.8V-3.7V to obtain the first discharge specific capacity, as shown in Table 1 below.

[0110] First discharge efficiency test

[0111] The prepared battery was subjected to a simple charge and discharge test at a current density of 20 mA / g. The first charge and discharge range was 2.8 to 4.4 V, and the first discharge efficiency was obtained, as shown in Table 1 below.

[0112] Table 1 Experimental parameters

[0113]

[0114] As can be seen from Table 1, when the sulfur compound is used alone and mixed with the lithium-containing metal oxide and heat-treated to prepare the positive electrode active material, as shown in Comparative Examples 1 to 5, as the amount of the sulfur compound mixed increases, the residual lithium gradually decreases. However, when the amount of the sulfur compound mixed increases to 0.5wt%, and further increases its content, the first discharge specific capacity and the first discharge efficiency of the battery will decrease, as shown in Comparative Examples 1 to 5. Figure 2 , Figure 3 , Figure 5 and Figure 6 As shown, it is mainly because when the sulfur compound continues to increase, the content of sulfur-containing compounds in the coating layer will also increase, and excessive sulfur-containing compounds will react with the electrolyte, thereby reducing the performance of the battery. Therefore, the preferred mixing amount range of the sulfur compound is 0.1wt% to 0.5wt%.

[0115] As shown in the data of Example 1 and Comparative Example 5 in Table 1, the residual LiOH content in Example 1 is higher than that in Comparative Example 5. The increase in residual lithium seems to be due to the mixing of B in Example 1. 2 O 3 , Li is generated during the heat treatment 3 BO 3 ,like Figure 4 As shown, during the residual alkali test, this substance consumes the HCl used to titrate LiOH, resulting in an apparent increase in the LiOH content.

[0116] As shown in Example 1 and Comparative Example 5, when sulfur compounds and boron compounds are mixed with lithium-containing metal oxides at the same time and heat-treated to prepare positive electrode active materials, the first discharge specific capacity of the battery is better than that of the sulfur compounds and lithium-containing metal oxides alone. The performance improvement is better. At the same time, according to the data analysis of Comparative Examples 2 to 4, when 1000 ppm of boron compounds are added to the lithium-containing metal oxides on the basis of Comparative Examples 2 to 4, and the positive electrode active materials are prepared by heat treatment, the first discharge specific capacity and the first discharge efficiency of the battery will be better than those of Comparative Example 5.

[0117] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A positive electrode active material, characterized in that: The positive electrode active material includes a lithium-containing metal oxide and a coating layer disposed on the surface of the lithium-containing metal oxide, wherein the coating layer includes a sulfur-containing compound and a boron-containing compound; The method for preparing the positive electrode active material comprises the following steps: The lithium-containing metal oxide is mixed with a boron compound and a sulfur compound, and subjected to heat treatment to obtain a positive electrode active material; the sulfur compound K2S x O y or Na2S x O y (x=1-8, y=1-8); the boron compound includes H3BO3 or B2O3; The mixing amount of the sulfur compound is in the range of 0.1wt% to 1.0wt%; The mixing amount of the boron compound ranges from 500 ppm to 2000 ppm.

2. The positive electrode active material according to claim 1, characterized in that The coating layer partially or completely coats the surface of the lithium-containing metal oxide.

3. The positive electrode active material according to claim 1 or 2, characterized in that The coating layer has a thickness of 1 nm to 500 nm.

4. The positive electrode active material according to claim 1, characterized in that The boron-containing compound includes lithium boron oxide, and the sulfur-containing compound includes lithium sulfur oxide and lithium sulfide.

5. The positive electrode active material according to claim 1 or 2, characterized in that The mixing amount of the sulfur compound is in the range of 0.1wt% to 0.5wt%; The mixing amount of the boron compound ranges from 500 ppm to 1000 ppm.

6. The positive electrode active material according to claim 1 or 2, characterized in that: The step of mixing the lithium-containing metal oxide with the boron compound and the sulfur compound and subjecting the mixture to heat treatment to obtain the positive electrode active material comprises the following steps: The lithium-containing metal oxide is dry-mixed with a boron compound and a sulfur compound, and subjected to heat treatment to obtain a positive electrode active material.

7. The positive electrode active material according to claim 1 or 2, characterized in that The step of mixing the lithium-containing metal oxide with the boron compound and the sulfur compound and subjecting the mixture to heat treatment to obtain the positive electrode active material comprises the following steps: The lithium-containing metal oxide is mixed with a boron compound and a sulfur compound, and heat-treated at a temperature of 100° C. to 600° C. in an air or oxygen atmosphere for 2 h to 10 h to obtain a positive electrode active material.

8. A battery, characterized in that: include: A negative electrode sheet, a positive electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises the positive electrode active material according to any one of claims 1 to 7.

9. An electrical device, characterized in that: The electrical device comprises the battery according to claim 8.

Citation Information

Patent Citations

  • Ternary positive electrode material, preparation method thereof and lithium ion battery

    CN112864385A

  • Composite coated positive electrode material and preparation method thereof

    CN113471411A

  • Covered cathode active material and lithium battery

    WO2015050031A1